Structural and Near-Infrared Properties of Nd3+ Activated Lu3NbO7 Phosphor - BAŞAK, ALİ SADİ; EKMEKÇİ, METE KAAN; ORALTAY, RIZA GÜRCAN (SPRINGER/PLENUM PUBLISHERS, 2017)
Undoped and Nd3+ doped lutetium niobate phases have been prepared by a conventional solid state reaction method using lutetium acetate and niobium oxide at 1250 A degrees C for 6 h. X-ray diffraction patterns of the 6 mol% Lu3NbO7 sample exhibited a cubic fluorite single phase. Phase structure exhibited interesting crystallization behaviour depending on increasing Nd3+ concentration which led to a Lu3NbO7 single phase formation during the heat treatment process. SEM investigations were also in agreement with the XRD results. Morphologies of Nd3+ doped lutetium niobate powders exhibited oval like shapes and grain sizes varied between 0.3 and 5 mu m. Near-infrared luminescence properties of Nd3+ doped Lu3NbO7 were also studied. 1.06 mu m laser transition characteristics of Nd3+ doped lutetium niobate have been observed. Concentration quenching phenomenon was not detected depending on increasing Nd3+ doping concentrations at room temperature.
Keywords: Ln(3)NbO(7); Niobates; Phosphors; Solid state synthesis; Neodymium doping; PHOTOLUMINESCENCE PROPERTIES; CRYSTAL-GROWTH; MAGNETIC-SUSCEPTIBILITY; PHOTOCATALYTIC ACTIVITY; TRANSPARENT LU3NBO7; THERMAL-PROPERTIES; LN(3)NBO(7) LN; PR; GD; LA